DINAMIKA HARGA DAN PERDAGANGAN KOMODITAS JAGUNG - BENNY RACHMAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
Corn price in Indonesia is quite related to corn price in the world market, exchange rate, andtrade policy. These aspects give some impact on domestic price stabilization policy. In linewith those issues, the objectives of this study are: (1) to analyze domestic and internationalcorn price prospective, (2) trade situation of corn commodity, and (3) to asses pricetransmission elasticity. Results of this study reply that corn price in the international markettend to decrease gradually. Growth of domestic corn price is affected by internationaleconomic condition i.e. international price and exchange rate. This case indicated by perfectlyprice transmission. Furthermore, to anticipate lower corn price in the international market andto support domestic producers, government should have implemented import tariffperiodically. In addition to support price policy, government should also consider theimprovement institutional aspects, such as marketing structure, farmers’ empowerment, andprice stabilization.